"There is no peace", "we are just persevering": triggers, manifestations, and consequences of intimate partner violence against men in Kenya - Waila, Jacinta; Mitiro, Domnick Onyango; Wilson, Michael; Horstick, Olaf; Musyimi, Christine Wayua (Journal of interpersonal violence, 2025)
Intimate partner violence (IPV) within heterosexual relationships affects both men and women, yet an in-depth description of IPV against men in developing countries is still limited. This study explored community perceptions of male IPV victimization in an informal settlement in Nairobi, Kenya. We conducted 12 focus group discussions (FGDs) with 118 ever-married participants (59 men and 59 women), divided into 6 FGDs for each gender. We performed thematic analysis using NVivo software. This article presents three main themes that emerged during data analysis: (a) triggers, (b) manifestations, and (c) consequences/effects of IPV against men. Both male and female participants perceived male IPV victimization as a significant concern in the community. The poor living conditions, coupled with alcohol use, seemed to be major underlying factors, often forming the basis of spousal conflict. Emotional abuse, including denial of basic needs, acts of humiliation, and coercive control, were the most frequently cited forms of violence. The consequences of what was considered IPV against men affected victims and their families including the violent female spouses, children, and the society at large. These effects upset the health, economic, and social spheres of life with some retriggering male IPV, thus creating a vicious cycle of abuse. Notably and of concern, IPV against women was highlighted as a consequence of male victimization. Although we set out to explore community perceptions, study participants openly shared their experiences of male IPV perpetration and victimization. These findings underscore the importance of recognizing men as potential victims of IPV and contextualizing IPV prevention strategies targeting the urban poor with the goal of designing and implementing policies and interventions that address IPV holistically.
Online veröffentlicht: 28. November 2024
Gesehen am 08.07.2025